CONSUMPTION OF COMMERCIALLY AVAILABLE VITAMIN D FORTIFIED FOODS AND SUPPLEMENTS AMONG MUSLIM WOMEN IN COIMBATORE CITY - B. HABEEBA* and C.A. KALPANA, (The Journal of Research ANGRAU, 2021)
Vitamin D fortification is an effective method to address the burden of Vitamin D deficiencyworldwide. The effectiveness of fortification greatly depends on the availability and consumption offortified foods. Thus, the study aims to identify commercially available Vitamin D fortified foods andsupplements and their consumption among muslim women in Coimbatore city. In a market survey of76 stores, selected by random sampling, data on the availability of fortified foods, cost, type andquantity of Vitamin D were recorded. Muslim women (n=225) between the age of 20–45 years wereselected as respondents. Details on their demographic profile, health status, knowledge of VitaminD, and consumption of fortified foods were collected. The findings revealed that 76 Vitamin D fortifiedproducts were available. Among these products, cereals and eggs provided >30 percent RDA ofVitamin D. A positive correlation existed between Vitamin D content and cost (P